La connaissance judiciaire des actes réglementaires - Barbe, Raoul (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
This paper describes the state of federal and Québec law as regards judicial notice of statutory instruments. The position in respect of federal instruments is first surveyed by reference to the provisions of the Canada Evidence Act and Canadian and British cases on the subject ; mention is then made of the now superseded Regulations Act of 1950 and the questions of interpretation that arose from it; and finally the impact of s. 23 of the Statutory Instruments Act of 1971 is evaluated in the light of the Supreme Court ruling in R. v. The « Evgenia Chandris ». The position in Québec law appears to be somewhat more confused. While the rule that regulations should be a matter for judicial notice seems well secured by s. 105 of the Summary Proceedings Act, this obviously only settles the point as regards penal proceedings under provincial statutes. In civil litigation, in the absence of any clear statement that regulations are to be judicially noticed, caution would seem to advise litigants to specifically plead and evidence the existence of regulations they intend to rely on. The author concludes by calling on the Québec Legislature to state explicitly the rule that regulations are a matter for judicial notice in any kind of proceedings.